Identifying the electron diffusion region in a realistic simulation of Earth's magnetotail. Issue 12 (24th June 2016) - Ashour‐Abdalla, Maha; Lapenta, Giovanni; Walker, Raymond; El‐Alaoui, Mostafa; Liang, Haoming; Zhou, Meng; Berchem, Jean; Goldstein, Melvyn L.
Abstract: A historic challenge to understanding geomagnetic activity is determining where in Earth's magnetotail magnetic energy is converted into particle energy and heat by magnetic reconnection. Key to unravel this fundamental process is in determining the location and extent of the electron diffusion region (EDR) where the energy conversion is initiated. We have located the EDR during a substorm on 15 February 2008 by using a combination of global magnetohydrodynamic (MHD) and particle‐in‐cell (PIC) simulations. Solar wind data were used as input into the MHD simulation, which provided the initial and boundary conditions for the PIC calculation. The simulated reconnection rate was episodic with magnetic reconnection occurring every few seconds. The reconnection site moved several Earth radii in a few minutes. A parameter that measures the breakdown of electron gyrotropy about the magnetic field provided the clearest location of the EDR where changes in magnetic topology and particle acceleration are initiated. Key Points: Electron agyrotropy provides the clearest indication of the EDR Reconnection is episodic occurring every few seconds The EDR can move several Earth radii in a few minutes